University Student’s Academic Goals When Working in Teams: Questionnaire on Academic Goals in Teamwork, 3 × 2 Model - León-del-Barco, Benito; Mendo-Lázaro, Santiago; Polo-del-Río, Ma Isabel; Rasskin-Gutman, Irina (Frontiers in Psychology, 2019)
Group work is a very common practice in higher education when it comes to developing key competences for students’ personal and professional growth. The goals that students pursue when working in teams determine how they organize and regulate their behavior and how they approach the tasks. The academic goals are a relevant variable that can condition the success of the group, as they guide and direct the students towards involvement in the task, the effort they make, and the desire to increase their academic competence, and their learning. Thus, the need arises to create new evaluation instruments to help us understand the importance of academic goals when students work as a team. The purpose of this paper is to corroborate the construct validity of the Questionnaire on Teamwork Learning Goals (QTLG) based on the Achievement Goal Questionnaire (3x2 AGQ) of Elliot, Murayama & Pekrun (2011) in the context of teamwork, and to determine if the model 3X2 offers a better fit to the data than other models, such as: 2x2; Trichotomous; Definition; Valence, among others. The results obtained from a sample of 700 students from 6 Spanish universities confirm that, in the context of teamwork, the 3x2 model fits the data better than the rest of the models subjected to confirmatory analysis, with contrasting evidence of validity and reliability. Therefore, we considered it a useful instrument for studying motivation in the group work context. The QTLG has practical applications, allowing us to explore in detail the academic goals of university students.